Giant axonal neuropathy: An updated perspective on its pathology and pathogenesis. Issue 4 (October 2014) - Johnson‐Kerner, Bethany L.; Roth, Lisa; Greene, J. Palmer; Wichterle, Hynek; Sproule, Douglas M.
ABSTRACT Giant axonal neuropathy (GAN) is a rare pediatric neurodegenerative disease. It is best known for the "giant" axons caused by accumulations of intermediate filaments. The disease is progressive, with onset around age 3 years and death by the third decade of life. GAN results from recessive mutations in the GAN gene encoding gigaxonin, and our analysis of all reported mutations shows that they are distributed throughout the protein structure. Precisely how these mutations cause the disease remains to be determined. In addition to changes in peripheral nerves that are similar to those seen in neuropathies such as Charcot–Marie–Tooth type 2, GAN patients exhibit a wide range of central nervous system signs. These features, corroborated by degeneration of central tracts apparent from postmortem pathology, indicate that GAN is also a progressive neurodegenerative disease. To reflect this phenotype more precisely, we therefore propose that the disease should be more appropriately referred to as "giant axonal neurodegeneration." Muscle Nerve50: 467–476, 2014